Acquired immunedeficiency syndrome in forensic autopsies - Prints, Carlos Delmonte; Mello, José Antonio de; Guidugli, Ruggero Bernardo; Cury, Conceição Gonçalves Caldeira (São Paulo Medical Journal, 1994)
From May 1985 to May 1989, 126 necropsies were performed at the São Paulo City Morgue on cadavers of individuals AIDS victims whose unnatural deaths had prompted police investigations. One hundred and nineteen males and 17 females were included. Ages were most commonly in the 20-to-30 year range. Fifty four deaths occurred in penal institutions, 29 deaths resulted from suicides, 17 deaths from manslaughter, 17 deaths were considered suspicious, 5 willful murders and 4 others also considered suspicious because corpses were found in advanced stages of putrefaction. Inmates, except one man who was strangled, died as a consequence of the disease. During all autopsies, special attention was paid to the high rate of extrapulmonary Mycobacterial infections. Suicides were committed in different ways and the majority of the victims were documented to be still in the initial stages of the disease. Suspicious deaths and deteriorated corpses were the result of negligence of the subject’s families. Homicidal deaths occurred in subjects in the terminal stages of the disease inside the hospital where these subjects were assisted and the immunedeficiency certainly contributed to aggravate the injuries leading to death. Attention is drawn to both legal and social issues affecting AIDS victims. The authors believe these issues may pose a hindrance for efficient control of the AIDS epidemic.